Pengaruh PAD dan DAU Terhadap Pengalokasian Belanja Modal - Hartiah, Permata Selly Pasa; Silalahi, Alistraja Dison (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to determine the effect of regional original income and general allocation funds on the allocation of capital expenditure in regencies/cities in North Sumatra Province. This type of research uses a quantitative associative approach and also uses secondary data. The population in this study were 33 districts/cities in North Sumatra. The data was obtained from the financial reports on the realization of the government budget and district/city regional spending in North Sumatera’s BPS Figures for 2018-2021. The method of determining the sample used is purpose sampling method. The results of the study show that regional original income has a significant effect on the allocation of capital expenditures, while general allocation funds have no significant effect on the allocation of expenditures. The results of the study when carried out jointly show that regional own-source revenues and general allocation funds have a significant effect on the allocation of capital expenditures.